Perkembangan dan Konsep Dasar Hubungan Masyarakat (Humas) dalam Dunia Pendidikan - Febriani, Vina Budi; Sulistiawati, Irma; Setiyadi, Bradley (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to describe the development and basic concepts of public relations (PR) in the world of education. The method applied is a qualitative research approach using literature study. The research results obtained are an understanding of community activities and relations, the role of work in the field of public relations, the importance of two-way communication in public relations, as well as the relationship between public relations and the public interest. The role of public relations (PR) in the world of education is very important because Public Relations contributes to achieving the goals of educational organizations through effective communication, fostering good relationships with stakeholders, and maintaining a good image and reputation.